Polygala obliqua Pendry, a new species of Polygalaceae from northern Thailand - Pendry, Colin A.; Adema, Frits (Thai Forest Bulletin (Botany), 2014)
Polygala obliqua Pendry (Polygalaceae) a new species from Tak Province is described and illustrated.